Effect of high intensity training on capillarization and presence of angiogenic factors in human skeletal muscle - Jensen, L (Blackwell Science Inc, 2004)
The effect of intense training on endothelial proliferation, capillary growth and distribution of vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF) was examined in human skeletal muscle. Two intermittent knee extensor training protocols (at ∼150% (Study 1) versus ∼90% (Study 2) of leg V˙(O(2))(max)) were conducted. Muscle biopsies were obtained throughout the training periods for immunohistochemical assessment of capillarization, cell proliferation (Ki-67-positive cells), VEGF and bFGF. In Study 1, microdialysis samples were collected from the trained and untrained leg at rest and during exercise and added to endothelial cells to measure the proliferative effect. After 4 weeks of training there was a higher (P < 0.05) capillary-to-fibre ratio (Study 1: 2.4 ± 0.1 versus 1.7 ± 0.1) and number of Ki-67-positive cells (Study 1: 0.18 ± 0.05 versus 0.00 ± 0.01) than before training. Neither the location of proliferating endothelial cells nor capillarization was related to muscle fibre type. The endothelial cell proliferative effect of the muscle microdialysate increased from rest to exercise in both the untrained leg (from 262 ± 60 to 573 ± 87% of control perfusate) and the trained leg (from 303 ± 75 to 415 ± 108% of perfusate). VEGF and bFGF were localized in endothelial and skeletal muscle cells and training induced no changes in distribution. The results demonstrate that intense intermittent endurance training induces capillary growth and a transient proliferation of endothelial cells within 4 weeks, with a similar growth occurring around type I versus type II muscle fibres.